(untitled) (Biocenosis, 2024)
The proper selection and use of native species in reforestation is essential for the restoration of ecosystems and the enhancement of urban-rural ecosystem services and significantly contributes to climate change adaptation. Since these species are adapted to local conditions, they promote ecosystem biodiversity and resilience, which favors a better response to extreme weather events. Planting native species helps reduce temperatures by creating cooler microclimates that mitigate the heat island effect. Additionally, they improve water infiltration by decreasing the risk of flooding and erosion. These species are also crucial for pollination, as many provide food for pollinators such as bees, which are fundamental for plant reproduction and food production. Incorporating these species is key to enhancing scenic beauty. Their presence in natural and urban environments beautifies the landscape and promotes people’s well-being and quality of life. The use of native species in reforestation not only boosts biodiversity, but also promotes carbon capture, improves air quality and regulates the water cycle; in other words, it preserves natural resources for future generations.